Collective Capabilities Complete a Neighbourhood: Community-engaged research and planning in South Vancouver - Bautista, Liza; Bouikidis, Aphrodite; Deol, Prabhi; Fassihi, Farina; Firth, Caislin; Holden, Meg; Rennie, Mimi; Sones, Meridith; Wong, Cherry (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2024)
This article argues for the need for attention to agency as well as structure in planning for complete neighbourhoods and communities, drawing upon collective capabilities theory and driven by a community-engaged research approach. While complete communities planning proposes to provide more fulsome social and physical infrastructure to residents in a context of urban growth and change in Canadian cities, contemporary efforts tend to neglect or disdain the agency and empowerment of residents. This logic and rationale for complete communities planning has shifted compared to the origins of neighbourhood planning in Canada, as will be exemplified here drawing upon the case of Vancouver. The application of the theory of collective capabilities in complete communities planning offers a path forward that is not naïve to the challenges posed by participatory planning and that views organizations other than the government as having collective capabilities to plan. We demonstrate the potential of this through the case of our community-engaged research partnership based at the South Vancouver Neighbourhood House. The project mobilized spatial and statistical research to document the extent of inequities and needs experienced in South Vancouver neighbourhoods as well as the collective capabilities of residents working through the neighbourhood house hub to provide essential services and do effective neighbourhood planning.